AN ANALYSIS OF MORAL VALUE IN THE MOVIE “AQUAMAN” DIRECTED BY JAMES WAN (2018) - Priyoto Priyoto; Irene Priskila (STIBA IEC JAKARTA, 2023)
This study aims to know the moral values and the types of moral values in Aquaman film. with moral approach. There are two research problems proposed from this “AQUAMAN” analyzing film. Based on the research problems, the researcher uses descriptive qualitative method in collecting the data. To analyze this film, the researcher applies moral value approach. There are two sources of data used to analyze the related issues, namely primary and secondary data sources. Primary data sources from the film Aquaman (2018) and other sources such as journals, websites, previous research, and other articles. In conclusion, the findings of this research shows there are many moral values found in the movie “AQUAMAN”, such as: love and affection, care, bravery, and sincerity. Then, Love, affection, care, bravery, and sincerity are very important parts of human life